Shaping Summertime Experiences: Opportunities to Promote Healthy Development and Well-Being for Children and Youth - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
For children and youth, summertime presents a unique break from the traditional structure, resources, and support systems that exist during the school year. For some students, this time involves opportunities to engage in fun and enriching activities and programs, while others face additional challenges as they lose a variety of supports, including healthy meals, medical care, supervision, and structured programs that enhance development. Children that are limited by their social, economic, or physical environments during the summer months are at higher risk for worse academic, health, social and emotional, and safety outcomes. In contrast, structured summertime activities and programs support basic developmental needs and positive outcomes for children and youth who can access and afford these programs. These discrepancies in summertime experiences exacerbate pre-existing academic inequities. While further research is needed regarding the impact of summertime on developmental domains outside of the academic setting, extensive literature exists regarding the impact of summertime on academic development trajectories. However, this knowledge is not sufficiently applied to policy and practice, and it is important to address these inequalities. Shaping Summertime Experiences examines the impact of summertime experiences on the developmental trajectories of school-age children and youth across four areas of well-being, including academic learning, social and emotional development, physical and mental health, and health-promoting and safety behaviors. It also reviews the state of science and available literature regarding the impact of summertime experiences. In addition, this report provides recommendations to improve the experiences of children over the summertime regarding planning, access and equity, and opportunities for further research and data collection.

Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Healthy mental, emotional, and behavioral (MEB) development is a critical foundation for a productive adulthood. Much is known about strategies to support families and communities in strengthening the MEB development of children and youth, by promoting healthy development and also by preventing and mitigating disorder, so that young people reach adulthood ready to thrive and contribute to society. Over the last decade, a growing body of research has significantly strengthened understanding of healthy MEB development and the factors that influence it, as well as how it can be fostered. Yet, the United States has not taken full advantage of this growing knowledge base. Ten years later, the nation still is not effectively mitigating risks for poor MEB health outcomes; these risks remain prevalent, and available data show no significant reductions in their prevalence. Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda examines the gap between current research and achievable national goals for the next ten years. This report identifies the complexities of childhood influences and highlights the need for a tailored approach when implementing new policies and practices. This report provides a framework for a cohesive, multidisciplinary national approach to improving MEB health.

A Roadmap to Reducing Child Poverty - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The strengths and abilities children develop from infancy through adolescence are crucial for their physical, emotional, and cognitive growth, which in turn help them to achieve success in school and to become responsible, economically self-sufficient, and healthy adults. Capable, responsible, and healthy adults are clearly the foundation of a well-functioning and prosperous society, yet America's future is not as secure as it could be because millions of American children live in families with incomes below the poverty line. A wealth of evidence suggests that a lack of adequate economic resources for families with children compromises these children's ability to grow and achieve adult success, hurting them and the broader society. A Roadmap to Reducing Child Poverty reviews the research on linkages between child poverty and child well-being, and analyzes the poverty-reducing effects of major assistance programs directed at children and families. This report also provides policy and program recommendations for reducing the number of children living in poverty in the United States by half within 10 years.

Monitoring Educational Equity - National Academies of Sciences, Engineering,; Medicine
Disparities in educational attainment among population groups have characterized the United States throughout its history. Education is sometimes characterized as the \

Multigenerational Approaches to Fostering Children's Health and Well-Being: The Opioid Crisis as a Case Study: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The opioid crisis is especially prevalent in rural and economically disadvantaged communities where poverty is associated with poor physical and mental wellbeing, health access is limited, opioid prescription rates are higher, and treatment programs are few. Children are one of the most vulnerable populations caught in this public health crisis, as a growing number are sent to live with other relatives or placed in foster care following the death of a parent or a parent's inability to continue as a primary caretaker while in recovery. Additionally, health care systems around the country have seen a dramatic increase in babies who are born with neonatal abstinence syndrome. All children affected by the opioid crisis, whether born with withdrawal symptoms or struggling as an older child surrounded by uncertainty, need dedicated attention, likely including specialized services, to achieve optimal levels of health and well-being. Unfortunately, because so many resources directed to the crises have been dedicated to the immediate and long-term needs of people who have overdosed, children often become a forgotten population. In response to this need, the Forum for Children's Well-Being convened a workshop in June 2019 on Fostering Children's Physical, Developmental and Social\/Behavioral Health in the Face of the Opioid Crisis. The goal of the workshop was to explore multigenerational approaches and policy strategies to promote health and well-being, using the opioid crisis as a case study. Multigenerational approaches and policy strategies that are successful in fostering children's health in this crisis may be adaptable in the future. This publication summarizes the presentation and discussion of the workshop.

Improving the American Community Survey: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Since its origin 23 years ago as a pilot test conducted in four U.S. counties, the U.S. Census Bureau2019s American Community Survey (ACS) has been the focus of continuous research, development, and refinement. The survey cleared critical milestones 14 years ago when it began full-scale operations, including comprehensive nationwide coverage, and 5 years later when the ACS replaced a long-form sample questionnaire in the 2010 census as a source of detailed demographic and socioeconomic information. Throughout that existence and continuing today, ACS research and testing has worked to improve the survey2019s conduct in the face of challenges ranging from detailed and procedural to the broad and existential. This publication summarizes the presentations and discussion at the September 26201327, 2018, Workshop on Improving the American Community Survey (ACS), sponsored by the U.S. Census Bureau. Workshop participants explored uses of administrative records and third-party data to improve ACS operations and potential for boosting respondent participation through improved communication.

Estimating the Prevalence of Human Trafficking in the United States: Considerations and Complexities: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
A 2-day public workshop on estimating the prevalence of human trafficking in the United States was held by the Committee on National Statistics in collaboration with the Committee on Population April 8-9, 2019. The workshop explored current and innovative sampling methods, technological approaches, and analytical strategies for estimating the prevalence of sex and labor trafficking in vulnerable populations. The workshop, sponsored by the Office on Women's Health at the Department of Health and Human Services (HHS), brought together statisticians, survey methodologists, researchers, public health practitioners, and other experts who work closely with human trafficking data or with the survivors of trafficking. Participants addressed the current state of research on human trafficking, advancements in data collection, and gaps in the data. They discussed international practices and global trends in human trafficking prevalence estimation and considered ways in which collaborations across agencies and among the U.S. government and private-sector organizations have advanced counter-trafficking efforts. The workshop highlighted the importance of understanding the scope of human trafficking in order to inform and receive support from policy makers and change agents.

A Decadal Survey of the Social and Behavioral Sciences: A Research Agenda for Advancing Intelligence Analysis - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The primary function of the intelligence analyst is to make sense of information about the world, but the way analysts do that work will look profoundly different a decade from now. Technological changes will bring both new advances in conducting analysis and new risks related to technologically based activities and communications around the world. Because these changes are virtually inevitable, the Intelligence Community will need to make sustained collaboration with researchers in the social and behavioral sciences (SBS) a key priority if it is to adapt to these changes in the most productive ways. A Decadal Survey Of The Social and Behavioral Sciences provides guidance for a 10-year research agenda. This report identifies key opportunities in SBS research for strengthening intelligence analysis and offers ideas for integrating the knowledge and perspectives of researchers from these fields into the planning and design of efforts to support intelligence analysis.

Methods to Foster Transparency and Reproducibility of Federal Statistics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In 2014 the National Science Foundation (NSF) provided support to the National Academies of Sciences, Engineering, and Medicine for a series of Forums on Open Science in response to a government-wide directive to support increased public access to the results of research funded by the federal government. However, the breadth of the work resulting from the series precluded a focus on any specific topic or discussion about how to improve public access. Thus, the main goal of the Workshop on Transparency and Reproducibility in Federal Statistics was to develop some understanding of what principles and practices are, or would be, supportive of making federal statistics more understandable and reviewable, both by agency staff and the public. This publication summarizes the presentations and discussions from the workshop.

Strengthening the Military Family Readiness System for a Changing American Society - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The U.S. military has been continuously engaged in foreign conflicts for over two decades. The strains that these deployments, the associated increases in operational tempo, and the general challenges of military life affect not only service members but also the people who depend on them and who support them as they support the nation 2013 their families. Family members provide support to service members while they serve or when they have difficulties; family problems can interfere with the ability of service members to deploy or remain in theater; and family members are central influences on whether members continue to serve. In addition, rising family diversity and complexity will likely increase the difficulty of creating military policies, programs and practices that adequately support families in the performance of military duties. Strengthening the Military Family Readiness System for a Changing American Society examines the challenges and opportunities facing military families and what is known about effective strategies for supporting and protecting military children and families, as well as lessons to be learned from these experiences. This report offers recommendations regarding what is needed to strengthen the support system for military families.

The Promise of Adolescence: Realizing Opportunity for All Youth - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Adolescence2014beginning with the onset of puberty and ending in the mid-20s2014is a critical period of development during which key areas of the brain mature and develop. These changes in brain structure, function, and connectivity mark adolescence as a period of opportunity to discover new vistas, to form relationships with peers and adults, and to explore one's developing identity. It is also a period of resilience that can ameliorate childhood setbacks and set the stage for a thriving trajectory over the life course. Because adolescents comprise nearly one-fourth of the entire U.S. population, the nation needs policies and practices that will better leverage these developmental opportunities to harness the promise of adolescence2014rather than focusing myopically on containing its risks. This report examines the neurobiological and socio-behavioral science of adolescent development and outlines how this knowledge can be applied, both to promote adolescent well-being, resilience, and development, and to rectify structural barriers and inequalities in opportunity, enabling all adolescents to flourish.

Interpersonal Violence Syndemics and Co-Occurring Epidemics: Preventing Violence in the Context of Opioid Misuse, Suicide, Social Disparities, and HIV: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The syndemics model is used to describe co-occurring epidemics that have a multiplicative effect on bodily systems through the adverse interaction of two or more diseases or health conditions. Additionally, in these situations, interactions with social conditions exacerbate both the prognosis and the burden of disease. There are two layers of interaction in this model2014the way diseases interact with each other and the way diseases are promoted by the social conditions in which people are living. It is important to understand this concept in order to create and implement effective multilevel preventive and intervention strategies that address these global public health issues by moving beyond the traditional silos of focusing on one epidemic. The National Academies of Sciences, Engineering, and Medicine convened a public workshop on May 16-17, 2019 to explore the syndemic model and three syndemics\/co-occuring epidemics. This includes 1) opioid use disorder (OUD), violence, suicide, and mental health in the United States, 2) adverse childhood experiences (ACEs) and childhood trauma; adult violence and victimization; and health outcomes from a global perspective, and 3) human immunodeficiency virus (HIV) and violence. The workshop participants considered the perspectives of survivors, researchers studying these interactions, public health professionals engaged with affected communities and in the creation and implementation of prevention and intervention measures, and policy makers who are seeking multilevel interventions. This publication briefly summarizes the presentations and discussions from the workshop.

Improving Care to Prevent Suicide Among People with Serious Mental Illness: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Suicide prevention initiatives are part of much broader systems connected to activities such as the diagnosis of mental illness, the recognition of clinical risk, improving access to care, and coordinating with a broad range of outside agencies and entities around both prevention and public health efforts. Yet suicide is also an intensely personal issue that continues to be surrounded by stigma. On September 11-12, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, to discuss preventing suicide among people with serious mental illness. The workshop was designed to illustrate and discuss what is known, what is currently being done, and what needs to be done to identify and reduce suicide risk. Improving Care to Prevent Suicide Among People with Serious Mental Illness summarizes presentations and discussions of the workshop.

Performance Management and Financing of Facility Engineering Programs at the Veterans Health Administration: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on May 8-9, 2019, to gather data on performance management and financing associated with the complex and diverse physical plants that support a wide variety of Veterans Health Administration (VHA) facilities. This workshop was the fourth in a series undertaken to assist the larger effort by an ad hoc committee of the National Academies for the Veterans Administration to prepare a resource planning and staffing methodology guidebook for VHA Facility Management (Engineering) Programs. This publication summarizes the presentations and discussions from the workshop.

Facilities Staffing Requirements for the Veterans Health Administration–Engineering Administration: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on March 5-6, 2019, to explore staffing considerations for engineering administration at the Veterans Health Administration (VHA) of the U.S. Department of Veterans Affairs (VA). Workshop speakers shared information about (1) data and data management, (2) contracting strategies, and (3) perspectives on challenges and expectations at various VHA facilities. This Proceedings of a Workshop2014in Brief summarizes the presentations and discussions that took place during the workshop.

Science and Engineering for Grades 6-12: Investigation and Design at the Center - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
It is essential for today's students to learn about science and engineering in order to make sense of the world around them and participate as informed members of a democratic society. The skills and ways of thinking that are developed and honed through engaging in scientific and engineering endeavors can be used to engage with evidence in making personal decisions, to participate responsibly in civic life, and to improve and maintain the health of the environment, as well as to prepare for careers that use science and technology. The majority of Americans learn most of what they know about science and engineering as middle and high school students. During these years of rapid change for students' knowledge, attitudes, and interests, they can be engaged in learning science and engineering through schoolwork that piques their curiosity about the phenomena around them in ways that are relevant to their local surroundings and to their culture. Many decades of education research provide strong evidence for effective practices in teaching and learning of science and engineering. One of the effective practices that helps students learn is to engage in science investigation and engineering design. Broad implementation of science investigation and engineering design and other evidence-based practices in middle and high schools can help address present-day and future national challenges, including broadening access to science and engineering for communities who have traditionally been underrepresented and improving students' educational and life experiences. Science and Engineering for Grades 6-12: Investigation and Design at the Center revisits America's Lab Report: Investigations in High School Science in order to consider its discussion of laboratory experiences and teacher and school readiness in an updated context. It considers how to engage today's middle and high school students in doing science and engineering through an analysis of evidence and examples. This report provides guidance for teachers, administrators, creators of instructional resources, and leaders in teacher professional learning on how to support students as they make sense of phenomena, gather and analyze data\/information, construct explanations and design solutions, and communicate reasoning to self and others during science investigation and engineering design. It also provides guidance to help educators get started with designing, implementing, and assessing investigation and design.

Achieving Behavioral Health Equity for Children, Families, and Communities: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In November 2017, the The Forum on Promoting Children's Cognitive, Affective, and Behavioral Health, in collaboration with the Roundtable on the Promotion of Health Equity, convened a workshop on promoting children's behavioral health equity. The workshop used a socio-ecological developmental model to explore health equity of children and families, including those with complex needs and chronic conditions. Particular attention was paid to challenges experienced by children and families in both rural and urban contexts, to include but not limited to poverty, individual and institutional racism, low-resourced communities, and hindered access to educational and health care services. Workshop participants also engaged in solution-oriented discussions of initiatives, policies, and programs that aim to improve social determinants of health, opportunities for behavioral health promotion, and access to quality services that address the behavioral health of all children and families. This publication summarizes the presentations and discussion of the event.

Increasing Student Success in Developmental Mathematics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The Board on Science Education and the Board on Mathematical Sciences and Analytics of the National Academies of Sciences, Engineering, and Medicine convened the Workshop on Increasing Student Success in Developmental Mathematics on March 18-19, 2019. The Workshop explored how to best support all students in postsecondary mathematics, with particular attention to students who are unsuccessful in developmental mathematics and with an eye toward issues of access to promising reforms and equitable learning environments. The two-day workshop was designed to bring together a variety of stakeholders, including experts who have developed and\/or implemented new initiatives to improve the mathematics education experience for students. The overarching goal of the workshop was to take stock of the mathematics education community's progress in this domain. Participants examined the data on students who are well-served by new reform structures in developmental mathematics and discussed various cohorts of students who are not currently well served - those who even with access to reforms do not succeed and those who do not have access to a reform due to differential access constraints. Throughout the workshop, participants also explored promising approaches to bolstering student outcomes in mathematics, focusing especially on research and data that demonstrate the success of these approaches; deliberated and discussed barriers and opportunities for effectively serving all students; and outlined some key directions of inquiry intended to address the prevailing research and data needs in the field. This publication summarizes the presentations and discussion of the workshop.

Reproducibility and Replicability in Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
One of the pathways by which the scientific community confirms the validity of a new scientific discovery is by repeating the research that produced it. When a scientific effort fails to independently confirm the computations or results of a previous study, some fear that it may be a symptom of a lack of rigor in science, while others argue that such an observed inconsistency can be an important precursor to new discovery. Concerns about reproducibility and replicability have been expressed in both scientific and popular media. As these concerns came to light, Congress requested that the National Academies of Sciences, Engineering, and Medicine conduct a study to assess the extent of issues related to reproducibility and replicability and to offer recommendations for improving rigor and transparency in scientific research. Reproducibility and Replicability in Science defines reproducibility and replicability and examines the factors that may lead to non-reproducibility and non-replicability in research. Unlike the typical expectation of reproducibility between two computations, expectations about replicability are more nuanced, and in some cases a lack of replicability can aid the process of scientific discovery. This report provides recommendations to researchers, academic institutions, journals, and funders on steps they can take to improve reproducibility and replicability in science.

Science Breakthroughs to Advance Food and Agricultural Research by 2030 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
For nearly a century, scientific advances have fueled progress in U.S. agriculture to enable American producers to deliver safe and abundant food domestically and provide a trade surplus in bulk and high-value agricultural commodities and foods. Today, the U.S. food and agricultural enterprise faces formidable challenges that will test its long-term sustainability, competitiveness, and resilience. On its current path, future productivity in the U.S. agricultural system is likely to come with trade-offs. The success of agriculture is tied to natural systems, and these systems are showing signs of stress, even more so with the change in climate. More than a third of the food produced is unconsumed, an unacceptable loss of food and nutrients at a time of heightened global food demand. Increased food animal production to meet greater demand will generate more greenhouse gas emissions and excess animal waste. The U.S. food supply is generally secure, but is not immune to the costly and deadly shocks of continuing outbreaks of food-borne illness or to the constant threat of pests and pathogens to crops, livestock, and poultry. U.S. farmers and producers are at the front lines and will need more tools to manage the pressures they face. Science Breakthroughs to Advance Food and Agricultural Research by 2030 identifies innovative, emerging scientific advances for making the U.S. food and agricultural system more efficient, resilient, and sustainable. This report explores the availability of relatively new scientific developments across all disciplines that could accelerate progress toward these goals. It identifies the most promising scientific breakthroughs that could have the greatest positive impact on food and agriculture, and that are possible to achieve in the next decade (by 2030).